Tuning the C1/C2 Selectivity of Electrochemical CO2 Reduction on Cu–CeO2 Nanorods by Oxidation State Control (Adv. Mater. 8/2023). Issue 8 (24th February 2023) - Hong, Seungwon; Abbas, Hafiz Ghulam; Jang, Kyuseon; Patra, Kshirodra Kumar; Kim, Beomil; Choi, Byeong‐Uk; Song, Hakhyeon; Lee, Kug‐Seung; Choi, Pyuck‐Pa; Ringe, Stefan; Oh, Jihun
Abstract : Electrochemical CO2 Reduction In article number 2208996, Pyuck‐Pa Choi, Stefan Ringe, Jihun Oh, and co‐workers report the synthesis of Cu–ceria‐nanorod catalysts for electrochemical CO2 reduction. The ceria nanorods help CuO exist as several cluster layers at the interface. Through the strong metal–support interaction between Cu and ceria, Cu can be stably loaded on ceria nanorods in a mixed oxidation state at the Cu/ceria interface, which facilitates CO–CO dimerization, resulting in high‐efficiency selective ethylene production.